A study on food handling behaviours and carrier status of bacterial food poisoning among food handlers in Dewan Bandaraya Ipoh Operational Area, Kinta District , Perak , 1996 - Meftahuddin Tarip; Osman Ali (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2006)
The cross-sectional study was carried out to determine the socio-demograpic factors i.e age, gender, ethnic groups, education level and working duration of food handlers. It is 'also aimed to determine the knowledge, attitude and practice of foodhandling and personal hygiene, carrier status ofbacteJ1al food poisoning and its risk factor, in Dewan Bandaraya Ipoh, Kinta District's operational area during February 1996. A total of 180 respondent were involved. The majority were Malay ethnic groups (72.2%), male (54.4%), secondary school and above education level (59.4%), has been working as food handlers for less than 5 years ( 56.1 %) and the mean age of respondents were 36.7 ± 12.9 years. The overall mean score for food handling knowledge was 22.3 ± 3.0 with percentage score of 85.7%. However the mean score for knowledge on food poisoning was low among Chinese ethnic groups and respondents with primary school or no formal education level (p<0.05 ). The mean score for knowledge on personal hygiene was low among male respondent (p<0.05). The overall mean score for attitude towards food handling was 14.4 ± 2.5 with percentage score of 80% and was low among Indian ethnic groups and respondents with age below 25 years old (p<0.05 ). The mean score for attitude towards hygienic practise of food handling was low among Chinese ethnic groups (p<0.05 ). The overall mean score for food handling practices was 16.1 ± 2.1 with percentage score of 84.2% and was low among male respondents, Chinese ethnic groups, age less then 41 years old, and working duration less than 5 years (p<0.05). The mean score for personal hygiene was 7.3± 1.4 and was low among Chinese ethnic groups, male respondents, and age less then 25 years old. The study showed that there was a significant,correlation (p<0.05) between knowledge, attitude and personal hygiene with food handling practices and by using multiple regression, an three factors still have significant correlation and were able to predict the food handling practices after controning other factors (p<0.05). The rate of carrier status for Staphylococcus aureus and Salmonella spp. was 8.3 % and the study showed that the carrier status has a significant correlation with personal hygiene and by using multiple logistic regression, it was shown that the personal hygiene still has significant correlation and was a predictive factor for can1er status (p<0.05). The information obtained from the study hopefully can be used as a reference to develop prevention and control strategies for food-borne diseases and intervention programme for food handlers.